Cutaneous leishmaniasis in cats (Felis domesticus) caused by Leishmania (Leishmania) venezuelensis - Bonfante Garrido, Rafael; Valdivia, Oswaldo; Torrealba, José; García, María; Garófalo, María; Urdaneta, lvan; Urdaneta, Rafael; Alvarado, Jorge; Copulillo, Elisa; Momen, Hooman; Grimaldi, Gabriel (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
In the search for reservoirs and other hosts of American cutaneous leishmaniasis (ACL) in Barquisimeto, Lara State, Venezuela, 4 cats (Felis domesticus) were found naturally infected with Leishmania, 3 in the suburb of El Carmen and 1 in San Francisco. The first (male) had a nodular lesion of a brownish red color, about 3.5 x 2.5 cm on the nose and other six nodules on the ears. The other three cats (females) each had a single diffuse lesión about 2 x 3 cm, with the same characteristics, on the nose. After three months metastases were observed al1 over the skin, this being more apparent on ears, extremities and tails. Smears made from all of the lesions, stained by the Giemsa method, contained abundant amastigotes both inside and outside histiocytes. The parasite isolated in hamsters and in NNN culture medium was identified by isoensyme electrophoresis and monoclonal antibodies as Leishmania (Leishmania) venezuelensis. The implications of these results with respect to both the clinical and epidemiological data are discussed.